2015
DOI: 10.1145/2700210
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Parameter Algorithms for Minimum-Cost Edge-Connectivity Augmentation

Abstract: We consider connectivity-augmentation problems in a setting where each potential new edge has a nonnegative cost associated with it, and the task is to achieve a certain connectivity target with at most p new edges of minimum total cost. The main result is that the minimum cost augmentation of edge-connectivity from k − 1 to k with at most p new edges is fixed-parameter tractable parameterized by p and admits a polynomial kernel. We also prove the fixed-parameter tractability of increasing edge-connectivity fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Further, we show that the unweighted case even admits a randomized polynomial kernel. All our results provide further interesting data points for the systematic study of connectivity-preservation constraints in the parameterized setting.1 Marx and Végh [13] compare [17] and [8] to [9] and [16] with respect to polynomial-time exact and approximation algorithms. 2 Note that since 1-vertex-connectivity is trivially equivalent to 1-edge-connectivity, the 1-vertexconnectivity case was proved to be FPT by Basavaraju et al [4].…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Further, we show that the unweighted case even admits a randomized polynomial kernel. All our results provide further interesting data points for the systematic study of connectivity-preservation constraints in the parameterized setting.1 Marx and Végh [13] compare [17] and [8] to [9] and [16] with respect to polynomial-time exact and approximation algorithms. 2 Note that since 1-vertex-connectivity is trivially equivalent to 1-edge-connectivity, the 1-vertexconnectivity case was proved to be FPT by Basavaraju et al [4].…”
mentioning
confidence: 80%
“…Nagamochi obtained an FPT algorithm for this problem while Guo and Uhlmann showed that this problem, alongside its vertex-connectivity variant, admits a quadratic kernel. Marx and Végh [13] studied the more general problem of augmenting the edge-connectivity of an undirected graph from λ − 1 to λ, via a minimum set of links that has a total cost of at most k, and obtained an FPT algorithm as well as a polynomial kernel for this problem. Basavaraju et al [3] improved the running time of their algorithm and further showed the fixed-parameter tractability of a dual parameterization of this problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While graph augmentation problems have been widely investigated (see [3,14]), their study from a parameterized complexity perspective is still at the beginning. Marx and Végh [20] proved that the problem of increasing the edge-connectivity of an undirected graph from k − 1 to k by adding at most B edges is fixed-parameter tractable when parameterized by B. They proposed an algorithm with complexity 2 O(B log B) |V | O (1) .…”
Section: Introductionmentioning
confidence: 99%